UTILIZATION OF PLANT EXTRACTS TO SUPPRESS Squash Mosaic Virus INFECTION ON RIDGED GOURD (Luffa acutangula [L.Roxb]) - Putri, Maharani Mustika; Damayanti, Tri Asmira (Universitas Lampung, 2020)
Utilization of plant extracts to suppress Squash Mosaic Virus Infection on ridged gourd (Luffa acutangula [L]. Roxb).Control effort strategies against plant pathogens are necessary to be explored and evaluated its effectiveness intensively.One environmentally friendly control method is biological control by using plant extracts. It is well known that cucurbits arecultivated widely in Indonesia. However, cucurbits are susceptible plants against various pathogens, including viruses.Recently, Squash mosaic virus (SqMV) found to infect cucurbits such as ridged gourd in West Java. The research aimed toexplore and evaluate the effectiveness of plant extracts to suppress SqMV infection on the ridged gourd. Three selectedplants, namely Bougainvillea spectabilis, Mirabilis jalapa, and Celosia cristata, were tested in greenhouse trial with aspirinas a comparison. The extract was sprayed on the leaves a day before mechanical virus infection. The disease assessments andagronomic parameters were observed. The plant extract treatment showed able to prolonged the incubation period, causedmilder symptoms, reduced the virus titer, and showed better plant growth in compared with aspirin treatment or untreatedcontrol. B. spectabilis and M. jalapa crude leaf extract revealed able to suppress the SqMV infection with comparableeffectiveness with relative inhibition level of disease severity and virus titer up to 48.2% and 80.6 to 81.4%, respectively,indicating their potential as biocontrol for SqMV.